A voxel‐based asymmetry study of the relationship between hemispheric asymmetry and language dominance in Wada tested patients. Issue 7 (23rd March 2018) - Keller, Simon S.; Roberts, Neil; Baker, Gus; Sluming, Vanessa; Cezayirli, Enis; Mayes, Andrew; Eldridge, Paul; Marson, Anthony G.; Wieshmann, Udo C.
Abstract: Determining the anatomical basis of hemispheric language dominance (HLD) remains an important scientific endeavor. The Wada test remains the gold standard test for HLD and provides a unique opportunity to determine the relationship between HLD and hemispheric structural asymmetries on MRI. In this study, we applied a whole‐brain voxel‐based asymmetry (VBA) approach to determine the relationship between interhemispheric structural asymmetries and HLD in a large consecutive sample of Wada tested patients. Of 135 patients, 114 (84.4%) had left HLD, 10 (7.4%) right HLD, and 11 (8.2%) bilateral language representation. Fifty‐four controls were also studied. Right‐handed controls and right‐handed patients with left HLD had comparable structural brain asymmetries in cortical, subcortical, and cerebellar regions that have previously been documented in healthy people. However, these patients and controls differed in structural asymmetry of the mesial temporal lobe and a circumscribed region in the superior temporal gyrus, suggesting that only asymmetries of these regions were due to brain alterations caused by epilepsy. Additional comparisons between patients with left and right HLD, matched for type and location of epilepsy, revealed that structural asymmetries of insula, pars triangularis, inferior temporal gyrus, orbitofrontal cortex, ventral temporo‐occipital cortex, mesial somatosensory cortex, and mesial cerebellum were significantly associated with the side of HLD. Patients with right HLD and bilateral language representation were significantly less right‐handed. These results suggest that structural asymmetries of an insular‐fronto‐temporal network may be related to HLD.